An Analysis Of Slang Used In The Film Inside Out 2 - Wina Dian Lestari; Nuzulul Isna (STMIK Indonesia Banda Aceh, 2025)
One of the problems in learning English as a foreign language (EFL) in Indonesia is students' lack of understanding the use of slang or casual language. This problem occur because learning in school generally emphasize grammar rather than casual use of everyday language, as often found in film or native conversations. Slang is usually difficult for students to understand because the context of its use is not always clear, and the meaning can be different from the literal meaning. In addition, the limited authentic partially open materials become an obstacle in presenting contextual and interesting learning. Based on this background, this study aims to analyze types of slang in the film Inside Out 2 and assess its potential as an authentic material to improve students' speaking skills. This research useds a qualitative method with a content analysis approach to the discourse script of the film to identify, classify, and interpret the use of various slang in each dialogue film. The results showed that there are various types of slang used naturally and according to the context of adolescent life, which are classified into five categories ; consiting of fresh and creative, flippant, imitative, acrinym, and clipping. For further research, it is suggested that the development of learning media be carried out by utilizing films that contain slang elements. This media can be a form of digital modules, interactive videos,or student worksheets (LKS) that include conversational exercises, context understanding, and active use of slang. This contextualized approach is believed to increase speaking ability and cultural understanding of native English speakers.